AB0082 CTLA4-IG/CD86 Interaction on Cultured Human Endothelial Cells: Evaluation of VEGF-R and ICAM-1 Protein Expression. (10th June 2014) - Cutolo, M.; Montagna, P.; Soldano, S.; Seriolo, B.; Contini, P.; Villaggio, B.; Brizzolara, R.
Abstract : Background: Endothelial cell (EC) dysfunction and angiogenesis are involved in synovitis in established rheumatoid arthtritis (RA) [1]. Some studies reported that the ECs express the repertoire of costimulatory molecules including CD86 (B7.2), for adequate T cell interaction/activation [2]. Our recent data showed that the fusion protein CTLA4-Ig (abatacept), used as biological agent in RA therapy, already interacts with the CD86 molecule expressed in synovial cells [3, 4]. Objectives: In the present study CTLA4-Ig/CD86 interaction and VEGF-R and ICAM-1 protein expression was evaluated in vitro on activated ECs. Methods: ECs (human microvascular endothelial cells, HMVEC, Lonza, Switzerland), after 7 days of culture, were induced by γ-IFN treatment (for 48 hours, 500 U/ml) to express CD86 molecules. Then, the cells were treated for 24 hours with CTLA4-Ig (10, 100, 500 μg/ml) and the protein expression of CD86, VEGF-R and ICAM-1 were evaluated by flow cytometric analysis (FACS). In addition, western blot analysis (WB) for VEGF-R and ICAM-1 protein expression were performed. Results: FACS analysis showed that, after CTLA4-Ig treatment (10, 100, 500 μg/ml), activated ECs decreased their CD86-positivity (66%, 59% and 51%, respectively), compared to untreated cells (68%), suggesting a CTLA4-Ig/CD86 interaction and masking on their surface. Therefore, almost all the activated ECs expressed VEGF-R (79%) and all activated ECs strongly expressed ICAM-1 (99%). After 24 hours of CTLA4-Ig treatment, the cells showed a decrease dose-dependent in the mean fluorescence value for ICAM-1, while VEGF-R positivity resulted unchanged. WB analysis for VEGF-R and ICAM-1 protein expression also showed a marked decrease in activated ECs treated with CTLA4-Ig at 500 μg/ml. Conclusions: The results observed at FACS analysis suggest an interaction between CTLA4-Ig and CD86 on activated ECs (expressing the CD86 molecule). In addition, a modulation in the expression of molecules relevant for the inflammatory and angiogenetic processes was observed. ICAM-1 protein expression shows on activated ECs a dose-dependent decrease after CTLA4-Ig treatment, at least for the higher dose treatment. Otherwise, VEGF-R protein expression showed a decrease only observed in WB analysis. In conclusion, ECs might be considered a further target for CTLA4-Ig in inflammatory conditions such as in presence of synovitis. References: Marrelli A et al. Autoimmun Rev. 2011;10(10):595-8. Kreisel D et al. J Immunol 2002;169(11):6154-61. Brizzolara R et al. Reumatismo. 2011;63(2):80-54. Cutolo M et al. Clin Exp Rheumatol. 2013;31(6):943-6. Disclosure of Interest: M. Cutolo Grant/research support: Bristol Myers Squibb, P. Montagna: None declared, S. Soldano: None declared, B. Seriolo Grant/research support: Bristol Myers Squibb, P. Contini: None declared, B. Villaggio: None declared, R. Brizzolara: None declared DOI: 10.1136/annrheumdis-2014-eular.3563